Effect of crevice corrosion inhibitors on the passivity of alloy 22 - Ortíz, Mauricio Rincón; Rodríguez, Martín Alejandro; Carranza, Ricardo Mario (Electrochemical Society, 2012)
Fil: Ortíz, Mauricio Rincón. The University Of Akron (uoa);